Pengaruh Akuntansi Pertanggungjawaban, Kompetensi, Dan Komitmen Organisasi Terhadap Kinerja Manajerial Pada Pt So Good Food Boyolali - Rejeqi, Tri Sri; Kusuma, Indra Lila; Dewi, Maya Widyana (Jurnal Ilmiah Keuangan Akuntansi Bisnis, 2025)
This study aims to analyze the effect of responsibility accounting, competence, and organizational commitment on managerial performance at PT So Good Food Boyolali. Managerial performance is an essential aspect because it reflects the effectiveness of managers in achieving organizational objectives. The study employed a quantitative approach with a survey method, involving 28 respondents who represented all managers in the company. Data were collected using questionnaires and analyzed through multiple linear regression. The results indicate that responsibility accounting and competence have a positive and significant effect on managerial performance, while organizational commitment does not show a significant influence. Simultaneously, the three variables significantly affect managerial performance with a coefficient of determination (R²) of 0.865, meaning that 86.5 percent of the variation in managerial performance is explained by the model, while the remaining 13.5 percent is influenced by other factors outside the model. These findings emphasize that managerial performance is largely determined by the effective implementation of responsibility accounting and adequate managerial competence.